2000
DOI: 10.1001/archpedi.154.3.294
|View full text |Cite
|
Sign up to set email alerts
|

Antecedents and Neonatal Consequences of Low Apgar Scores in Preterm Newborns

Abstract: Low Apgar scores are associated with increased neonatal morbidity and mortality in preterm newborns. Antenatal maternal history, and pregnancy complications are not clearly associated with low Apgar scores. Therefore, the Apgar score is a useful tool in assessing neonatal short-term prognosis and the need for intensive care among preterm newborns.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
37
0
2

Year Published

2002
2002
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 29 publications
5
37
0
2
Order By: Relevance
“…The absence of any significant differences in low Apgar scores lends support to the findings in another study that antenatal maternal history and pregnancy complications (such as pre-eclampsia and vaginal bleeding) and events in labour like the use of oxytocin, magnesium and narcotics are not clearly associated with low Apgar scores 24 .…”
Section: Discussionsupporting
confidence: 76%
“…The absence of any significant differences in low Apgar scores lends support to the findings in another study that antenatal maternal history and pregnancy complications (such as pre-eclampsia and vaginal bleeding) and events in labour like the use of oxytocin, magnesium and narcotics are not clearly associated with low Apgar scores 24 .…”
Section: Discussionsupporting
confidence: 76%
“…It is more difficult to clinically assess encephalopathy in very premature infants than at term; however, larger premature infants from 31 to 36 weeks gestation with metabolic acidosis in cord blood do have a high rate of evolving clinical encephalopathy after birth, which in turn is associated with adverse neurological outcome (Salhab and Perlman, 2005). Consistent with this, in the wider population of premature infants, adverse neonatal and long-term outcomes are strongly associated with evidence of exposure to perinatal hypoxia as shown by metabolic acidosis, active labor, abnormal heart rate traces in labor, and subsequent low Apgar scores (Low et al, 1995;de Vries et al, 1998;Weinberger et al, 2000;Osborn et al, 2003;Bell et al, 2005).…”
Section: Timing and Etiology Of Preterm Brain Injurymentioning
confidence: 80%
“…Nevertheless, there is some evidence for a role of subtle insults, as shown, e.g., by depressed Apgar scores at birth (22). More recently, the Extremely Low Gestational Age Newborns (ELGAN) study reported that severe intrauterine growth restriction and evidence of placental vascular thrombosis consistent with longstanding, prenatal hypoxemia were associated with impaired neurodevelopmental outcome at 2 y of age (23).…”
Section: Timing and Etiology Of Preterm Brain Injurymentioning
confidence: 99%